Penentuan Kadar Flavonoid dan Kandungan Fitokimia Ekstrak Kulit Bawang Merah (Allium cepa L) dengan Berbantukan Microwave sebagai Potensi Bahan Aktif Tabir Surya - Dalimunthe, Nisaul Fadilah; M. Thoriq Al Fath; Taslim; S. Ginting, M. Hendra; Farah Nurul Alifia; Berta, Grace Adela (Talenta Publisher (Universitas Sumatera Utara), 2024)
The skin serves as a protective barrier against dust and ultraviolet (UV) radiation. Excessive UV exposure is associated with accelerated skin aging, erythema, hyperpigmentation, and carcinogenesis. This study aimed to quantify flavonoid concentrations and characterize phytochemical constituents in shallot skin extracts for their potential as active ingredients in sunscreen formulations. Shallot skin was subjected to microwave assisted extraction using 70% ethanol as the solvent. Phytochemical screening revealed the presence of flavonoids, tannins, saponins, and alkaloids in the extract. Flavonoid content was determined via UV-Vis spectrophotometry, yielding 36.33 mgQE/g. The high flavonoid concentration observed in shallot skin extract suggests its potential efficacy as an active ingredient in sunscreen formulations.